2007
DOI: 10.1007/s00125-007-0874-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary protein restriction on albumin and fibrinogen synthesis in macroalbuminuric type 2 diabetic patients

Abstract: Aims/hypothesis Diabetic nephropathy is associated with hypoalbuminaemia and hyperfibrinogenaemia. A lowprotein diet has been recommended in patients with diabetic nephropathy, but its effects on albumin and fibrinogen synthesis are unknown. Methods We compared the effects of a normal (NPD; 1.38± 0.08 g kg −1 day −1 ) or low (LPD; 0.81±0.04 g kg −1 day −1 ) -protein diet on endogenous leucine flux (ELF), albumin and fibrinogen synthesis (L-[5,5,5,-2 H 3 ]leucine infusion), and markers of inflammation in nine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…The assessment of the fibrinogen synthesis rate in the present study is a needed addition to the small number of publications detailing the de novo synthesis of fibrinogen in humans [7, 8, 19, 22, 23, 3234]. The quantitative values of our results are in agreement with these prior publications.…”
Section: Discussionsupporting
confidence: 90%
“…The assessment of the fibrinogen synthesis rate in the present study is a needed addition to the small number of publications detailing the de novo synthesis of fibrinogen in humans [7, 8, 19, 22, 23, 3234]. The quantitative values of our results are in agreement with these prior publications.…”
Section: Discussionsupporting
confidence: 90%
“…Limiting protein waste products can lead to less uremic toxin elaboration and less toxin-induced inflammation. The positive effects of moderate dietary protein restriction on inflammatory state (IL-6) have been shown in proteinuric diabetic patients [161]. The intestinal source of inflammation can be minimized by preventing dysbiosis through increasing dietary fiber, appropriate treatment of constipation in addition to an adequate dietary provision of protein and energy.…”
Section: Clinical Recommendationsmentioning
confidence: 99%
“…Thus, the treatment strategies for renal failure, including the use of protein-restricted diets [1], have gained increased interest for the treatment of patients with diabetic nephropathy. Despite the few studies that suggest that protein intake restriction fails to improve renal prognosis in type 1 or type 2 diabetic patients with incipient or overt nephropathy[2] and confers renoprotection[3], several findings have demonstrated that a low-protein diet preserves renal function and structure in animal models [4] and in type 2 diabetic patients with macroalbuminuria[5] and improves disease prognosis[6], low-grade inflammation and proteinuria[7] and depressive symptoms[8]. However, there has been increasing concern regarding the risk of the subsequent development of malnutrition due to these diets.…”
Section: Introductionmentioning
confidence: 99%